2018
DOI: 10.1007/s12015-018-9836-7
|View full text |Cite
|
Sign up to set email alerts
|

A Circadian Rhythm in both Complement Cascade (ComC) Activation and Sphingosine-1-Phosphate (S1P) Levels in Human Peripheral Blood Supports a Role for the ComC–S1P Axis in Circadian Changes in the Number of Stem Cells Circulating in Peripheral Blood

Abstract: The number of hematopoietic stem/progenitor cells (HSPCs) circulating in peripheral blood (PB) is regulated by a circadian rhythm, and more HSPCs circulate in PB in the morning hours than at night. Different mechanisms have been proposed that might regulate this process, including changes in tonus of β-adrenergic innervation of bone marrow (BM) tissue. Our group reported that in mice circadian changes in the number of HSPCs circulating in PB correlates with diurnal activation of the complement cascade (ComC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 58 publications
(60 reference statements)
3
24
0
Order By: Relevance
“…Melatonin levels in plasma samples were measured by using an enzyme-linked immunoassay (enzyme-linked immunosorbent assay kit, Cloud-clone Corp., Houston, TX) according to the manufacturer's protocol. 20 Briefly, 50 μL of the plasma samples and the serially diluted standards were applied into the each well, and each reagent was added and incubated and then measured at 450 nm with a microplate reader (SpectraMax i3, Molecular Devices, Sunnyvale, CA). The concentrations of the melatonin were calculated by using the standard curve.…”
Section: Subjects and Study Protocolmentioning
confidence: 99%
“…Melatonin levels in plasma samples were measured by using an enzyme-linked immunoassay (enzyme-linked immunosorbent assay kit, Cloud-clone Corp., Houston, TX) according to the manufacturer's protocol. 20 Briefly, 50 μL of the plasma samples and the serially diluted standards were applied into the each well, and each reagent was added and incubated and then measured at 450 nm with a microplate reader (SpectraMax i3, Molecular Devices, Sunnyvale, CA). The concentrations of the melatonin were calculated by using the standard curve.…”
Section: Subjects and Study Protocolmentioning
confidence: 99%
“…Interestingly, we also demonstrated that the plasma level of S1P fluctuates in patients in a circadian rhythm-dependent manner, with the peak in the early morning hours and the nadir late at night [8]. This fluctuation in S1P level can be explained by activation of the ComC due to hypoxia during deep sleep, which by generating C5b-C9 (also known as membrane attack complex, MAC) releases S1P from red blood cells and activated platelets [8].…”
Section: Discussionmentioning
confidence: 67%
“…The circadian changes in the number of circulating HSPCs in PB were the subject of several excellent studies showing a peak in the early morning hours and a nadir at night [5][6][7][8][9][10][11][12][13]. This phenomenon has been attributed to diurnal changes in tonus of the vegetative nerves that innervate BM tissue as a result of external light and dark cycles [4,9,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations